Pembuktian Tindak Pidana Intimidasi Melaui Media Sosial (Cyberbullying) - Ni Nyoman Ayu Pramita Dewi; Simon Nahak; I Made Minggu Widyantara (Jurnal Analogi Hukum, 2021)
The problem faced by law enforcers to ensnare suspected Cyberbullying crimes is proof of the defendant's mistake. Electronic evidence is not recognized as valid evidence in the Criminal Procedure Code, but in practice electronic evidence is acknowledged as valid. The formulation of this research problem is: (1) How is the handling of mayantara crime (Cyberbullying) based on UU.RI.No 11 of 2008 concerning ITE (2) How is the proof of the crime of mayantara in accordance with applicable law in Indonesia? This writing uses a normative approach with the method of law approach, conceptual approach and case approach. The results show that: (1) Cyberbullying is a new type of crime with electronic means and in Indonesia itself is included in the category of defamation. The legal certainty of Cyberbullying is in article 27 paragraph (3) not in the provisions of article 310 of the Criminal Code based on the Constitutional Court Decision No. 50 / PUU-VI / 2008, Decision of the Constitutional Court No50-PUU-VI / 2008 confirms a Legal Certainty on Cyberbullying provisions. (2) in the system of proof of criminal acts of Cyberbullying which is still guided by the Criminal Procedure Code which in this case has not recognized electronic evidence as a legitimate evidence, but the use of electronic evidence as legal evidence is still used in some judicial practices, in special laws so the creation of material truth.